Competing destinations gravity model applied to trade in intermediates - de Mello-Sampayo, F. (Applied Economics Letters, 2017)
The competing-destinations formulation of the gravity model ensues from the fact that unlike the classic version, this approach explicitly acknowledges the interdependence of the flows between a set of alternative countries. This paper applies the competing-destinations gravity model to the analysis of trade in intermediate goods. The results of the model were then tested empirically with an international input-output dataset and using the PPML estimator. The empirical results suggest that the analytical model can explain trade in intermediate goods. Indeed, as predicted, import of intermediate goods is increasing in the importing country's demand for inputs, in the competitiveness of the exporting country, and decreasing in distance and competition posed by alternative countries.